Treating hallucinations in Parkinson's disease. (3rd June 2022) - Powell, Alice; Matar, Elie; Lewis, Simon J. G.
ABSTRACT: Introduction: Hallucinations in Parkinson's disease are common, can complicate medication management and significantly impact upon the quality of life of patients and their carers. Areas covered: This review aims to examine current evidence for the management of hallucinations in Parkinson's disease. Expert opinion: Treatment of hallucinations in Parkinson's disease should be both individualized and multifaceted. Screening, education, medication review and the avoidance of common triggers are important. For well-formed visual hallucinations, acetylcholinesterase inhibitors are recommended first-line. Refractory or severe symptoms may require the cautious use of atypical antipsychotics. Antidepressants may be beneficial in the appropriate setting. Unfortunately, current therapies for hallucinations offer only limited benefits and future research efforts are desperately required to improve the management of these challenging symptoms.